Characterization of single phase Pt-doped Zn 2TiO 4 nanoparticles synthesized by flame spray pyrolysis - Chawarat Siriwong (2018)
Single phase undoped Zn2TiO4and Zn2TiO4nanoparticles doped with 0.25-1.00 mol% Pt were successfully synthesized in a single step by the flame spray pyrolysis (FSP) technique. Zinc naphthenate and titanium tetra isopropoxide (1:1 mol%); and platinum (II) acetylacetonate were used as Zn, Ti and Pt precursors respectively dissolved in ethanol. The undoped Zn2TiO4and Pt-doped Zn2TiO4nanoparticles were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM) and energy dispersive spectroscopy (EDS). The BET surface area (SSABET) of the nanoparticles was measured by nitrogen adsorption. The average diameter of the spherical nanoparticles were in the range of 5.7-6.9 nm under 5/5 (precursor/oxygen) flame conditions. All peaks can be confirmed to correspond to the cubic structure of Zn2TiO4(JCPDS No. 25-1164). © 2011 Elsevier B.V. All rights reserved.